2019
DOI: 10.1039/c9me00007k
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-layer integration of conducting polymers and metal organic frameworks onto electrode surfaces: enhancement of the oxygen reduction reaction through electrocatalytic nanoarchitectonics

Abstract: Nanoarchitectonics can lead to electrode materials with enhanced electrocatalytic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…In recent years, the modification of solid‐state nanopores via polyelectrolyte assembly/adsorption has gained increasing interest . The LbL assembly of polyelectrolytes represents a very simple and versatile chemical method to create functional thin films with nanoscale precision . This functionalization method is based on the alternate deposition of polyanions and polycations on solid surfaces leading to the formation of polyelectrolyte multilayers .…”
Section: Functionalization Of Solid‐state Nanoporesmentioning
confidence: 99%
“…In recent years, the modification of solid‐state nanopores via polyelectrolyte assembly/adsorption has gained increasing interest . The LbL assembly of polyelectrolytes represents a very simple and versatile chemical method to create functional thin films with nanoscale precision . This functionalization method is based on the alternate deposition of polyanions and polycations on solid surfaces leading to the formation of polyelectrolyte multilayers .…”
Section: Functionalization Of Solid‐state Nanoporesmentioning
confidence: 99%
“…Azzaroni, Rafti, and co‐workers demonstrated the hierarchic integration of conductive polymers with MOF structures using LbL assembly as a nanoarchitectonics essence ( Figure ). [ 76 ] Fabrication of these hierarchical nanostructures started from synthesis of two kinds of colloidal assemblies: anionic polyaniline (PANI)/poly(styrene sulfonate) (PSS) colloidal particles and zeolitic imidazolate framework‐8 (ZIF‐8) colloidal particles modified with cationic poly(allylamine hydrochloride) (PAH). These electrically opposite colloidal substances were then assembled into nanoarchitected thin films by the LbL assembly.…”
Section: Evolution From Atom/molecule To Materials With Nanoarchitectomentioning
confidence: 99%
“…In 2017, the Dincaˇ group prepared Ni 3 (HITP) 2 as an electrode material for the electrochemical capacitors (EC), [ 17 ] and found that this material has excellent capacitance. This major discovery has inspired scientists to explore applications of the conductive MOFs in the field of electrochemistry, including chemical resistance sensors, [ 18–20 ] supercapacitors, [ 21–24 ] electrocatalysis, [ 25–27 ] and electronic devices. [ 28–30 ]…”
Section: Introductionmentioning
confidence: 99%